Prevalência de obesidade e fatores associados em idosos do sul do Brasil - Pizolotto, Renata Sebastiana de Souza (2018)
The rapidity that life expectancy increases impresses, but it has brought together challenges of healthy and active aging. In this context, it was necessary to evaluate the obesity and associated factors in a city in the south of Brazil. This is a cross-sectional, observational, home-based study in the age group between 65 and 74 years old, living in residential homes in the city of Cruz Alta / RS. Two criteria were used to evaluate obesity: one based on BMI for the elderly and another based on BMI / WHO. Associations between the dependent variable and independent variables were assessed by chi-square or Mann-Whitney tests. Univariate and multivariate analyzes were performed using Poisson regression with robust variance. 287 elderly people were interviewed and examined. The mean age was 69.30 years (SD ± 3.52), of which 102 (35.5%) were male and 185 (64.5%) were female. Regarding ethnicity / skin color, 196 (68.3%) declared themselves white and 91 (31.7%) reported being nonwhite. In relation to the educational level, 190 (62.6%) had low educational level, of which, 17 (5.9%) declared themselves illiterate. Thus, the results will be presented in the production I. Conclusions The findings of this study demonstrated a high prevalence of obesity in the elderly, which were associated with demographic and behavioral factors. The results suggest the need for an improvement in lifestyle and public policies that care about prevention.